Hydroxyurea use in Children with Sickle Cell Disease: Do Severely Affected Patients Use It and Does It Impact Hospitalization Outcomes?. Issue 5 (21st January 2016) - Creary, Susan E.; Chisolm, Deena J.; Koch, Terah L.; Zigmont, Victoria A.; Lu, Bo; O'Brien, Sarah H.
Abstract : Background: Expert guidelines recommend that hydroxyurea (HU) be offered to all children with hemoglobin SS and Sβ 0 sickle cell disease (SCD) and be considered for children with clinically severe hemoglobin SC or Sβ + . This study aims to determine the rate of HU use in hospitalized children, if HU is differentially used in children with clinically severe SCD, and if HU users have shorter length of stay (LOS), fewer intensive care unit (ICU) admissions, and fewer inpatient transfusions compared to nonusers. Procedure: Using the Pediatric Health Information System, we performed a retrospective analysis of children ages 2–18 years with SCD discharged between January 1, 2011 and September 30, 2014. We defined patients as having clinically severe SCD if they had a recent ICU admission or ≥3 admissions in the preceding year. Results: Of the 2, 665 unique children identified, approximately 80% had an inpatient code indicating HU use. Significantly more ( p < 0.001) nonusers (30.1%) had a recent ICU admission compared to HU users (18.7%). More nonusers (33.9%) had a history of ≥3 admissions compared to HU users (21.5%) ( p < 0.001). After applying propensity score weighting, the groups did not differ in their LOS, prevalence of ICU admissions, or prevalence of transfusions. Conclusions: HU use is high among hospitalized children with SCD. However, HU is not utilized by many children with clinically severe SCD. These results support that HU be considered in children with SCD to prevent hospitalization rather than as a treatment to improve hospitalization outcomes.